1996
DOI: 10.1093/gerona/51a.5.m247
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Strength and Endurance in Different Aged Individuals

Abstract: The results of this study suggest that tongue function is gender- and age-dependent and follows the same trends as hand function. Tongue strength is decreased in older individuals and females, while tongue endurance is gender- and age-independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
190
3
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(225 citation statements)
references
References 13 publications
25
190
3
7
Order By: Relevance
“…Common are reports of decreased skeletal muscle strength, muscle atrophy and increased muscle fatigability (Campbell, McComas, & Petito, 1973;Price, & Darvell, 1981;Wilder, 1984;Sonies, 1991;Crow, & Ship, 1996;Martini, 1998). Declines in sensory and motor nerve conduction velocity, motor unit loss, and a slowing of fine and gross motor movements (LaFratta, & Canestrari, 1966;Brown, 1972;Sonies, 1991) have also been observed, as have changes to the skeletal system, with bone loss and changes in bone composition (Sonies, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common are reports of decreased skeletal muscle strength, muscle atrophy and increased muscle fatigability (Campbell, McComas, & Petito, 1973;Price, & Darvell, 1981;Wilder, 1984;Sonies, 1991;Crow, & Ship, 1996;Martini, 1998). Declines in sensory and motor nerve conduction velocity, motor unit loss, and a slowing of fine and gross motor movements (LaFratta, & Canestrari, 1966;Brown, 1972;Sonies, 1991) have also been observed, as have changes to the skeletal system, with bone loss and changes in bone composition (Sonies, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related changes in tongue structure and function include findings of muscle atrophy (Bassler, 1987), reductions in strength (Price, & Darvell, 1981;Robbins et al, 1995;Crow, & Ship, 1996), slower movements and reduced regularity in the rhythm of tongue movements (Hirai, Tanaka, Koshino, & Yajima, 1991). Increases in fatty tissue (lipomatosis) in the musculature of the tongue (Bassler, 1987), together with a narrowing of muscle fibres and fibrosis of the perimysium (Bassler, 1987) have also been found with increased age.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of OSA increases with age; 2-to 3-fold higher prevalence in older persons (≥65 years) compared to middle aged persons (30-64 years) [33]. Old age is often accompanied by muscular and neurological loss of muscle tone of the upper airway with enhanced collapsibility, thus increasing risk for OSA [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies have found a relationship between increasing of age and decreasing of tongue force (2,(14)(15)(16)18) . However, the strength reduction only occurs after age 60 (12)(13)(14) justifying the non stratification of the sample by age.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies found greater force in men (2,6,13,(15)(16)(17) . However, in other studies such difference was not observed (12,14,(18)(19)(20)(21)(22) .…”
Section: Introductionmentioning
confidence: 99%